Context-free word problem semigroups - Brough, Tara (2020)
fellowship SFRH/BPD/121469/2016. The second author was supported by the ‘Investigador FCT’ fellowship IF/ 01622/2013/CP1161/CT0001. For the first and second authors, this work was partially supported by FCT projects UID/MAT/00297/2019. PTDC/MHC-FIL/2583/2014 and PTDC/MAT-PUR/31174/2017. This work was started during a visit by the third author to the Universidade Nova de Lisboa, which was supported by the exploratory project IF/01622/2013/ CP1161/CT0001 attached to the second author’s research fellowship.